The co-occurrence of multisensory competition and facilitation. - Sinnett, S; Soto-Faraco, S; Spence, C (2008)
Previous studies of multisensory integration have often stressed the beneficial effects that may arise when information concerning an event arrives via different sensory modalities at the same time, as, for example, exemplified by research on the redundant target effect (RTE). By contrast, studies of the Colavita visual dominance effect (e.g., [Colavita, F. B. (1974). Human sensory dominance. Perception and Psychophysics, 16, 409-412]) highlight the inhibitory consequences of the competition between signals presented simultaneously in different sensory modalities instead. Although both the RTE and the Colavita effect are thought to occur at early sensory levels and the stimulus conditions under which they are typically observed are very similar, the interplay between these two opposing behavioural phenomena (facilitation vs. competition) has yet to be addressed empirically. We hypothesized that the dissociation may reflect two of the fundamentally different ways in which humans can perceive concurrent auditory and visual stimuli. In Experiment 1, we demonstrated both multisensory facilitation (RTE) and the Colavita visual dominance effect using exactly the same audiovisual displays, by simply changing the task from a speeded detection task to a speeded modality discrimination task. Meanwhile, in Experiment 2, the participants exhibited multisensory facilitation when responding to visual targets and multisensory inhibition when responding to auditory targets while keeping the task constant. These results therefore indicate that both multisensory facilitation and inhibition can be demonstrated in reaction to the same bimodal event.